Poverty Reduction and Growth Trust : 2017 Borrowing Agreements with the Bank of Italy. (Policy Papers; Policy Paper, 2017)
On July 17, 2017, the Fund, as Trustee of the Poverty Reduction and Growth Trust (PRGT or Trust), entered into a new borrowing agreement (the 'Agreement') with the Bank of Italy (hereafter, Italy or Purchaser), by which Italy will provide new resources to the Extended Credit Facility Loan Account of the PRGT in the total amount of up to SDR 400 million.